Broad sampling and diverse biomarkers allow characterization of nearshore particulate organic matter. Issue 11 (17th June 2014) - Lowe, Alexander T.; Galloway, Aaron W. E.; Yeung, J. Sean; Dethier, Megan N.; Duggins, David O.
<x xml:space="preserve">Abstract</x> Suspended particulate organic matter (POM) is a primary food source for benthic and pelagic consumers in aquatic and marine ecosystems. POM is potentially composed of many sources including phytoplankton, bacteria, zooplankton and macrophyte (seaweed and seagrass) and terrestrial detritus. The relative importance of these sources to POM consumers is debated, in large part due to differing interpretations of stable isotope and fatty acid biomarkers. We investigated POM composition in a nearshore marine ecosystem using multiple methods including visual quantification of living and detrital components, multiple stable isotope (MSI) and fatty acid (FA) analyses. Sampling was conducted at multiple temporal and spatial scales to 1) determine the range of variability in POM biomarkers, 2) quantitatively evaluate δ13C, δ15N, δ34S and FA biomarkers with proportional abundance of putative sources and 3) determine the availability of phytoplankton, macrophytes and terrestrial carbon in nearshore POM. Variation of total FA concentration and proportions, and δ13C and δ34S were strongly correlated to phytoplankton abundance, at tidal and seasonal timescales. Using multivariate multiple regressions, MSI and FA explained 59.6% and 89.7% of the variation in POM composition, respectively. As phytoplankton abundance increased, total FA concentration increased concurrent to δ13C and δ34S enrichment. In high detritus samples, bacterial FA and saturated FA were proportionally higher, corresponding to depletion of δ13C and δ34S and enrichment of δ15N. We identify MSI and FA biomarkers that are good predictors of diatom, dinoflagellate and detrital contributions to the POM. The results of this multi‐scale study show that POM composition is highly dynamic and largely driven by phytoplankton abundance, with minor contributions from terrestrial or macrophyte subsidies. This quantitative approach provides novel and critical empirical information linking POM compositional dynamics to specific biomarkers that are commonly used for tracking energy subsidies and biogeochemical cycling in aquatic ecosystems.